GENDERED ACTIVITY MAPPING ACROSS HIERARCHIES OF URBAN GREEN SPACES: A CASE OF DELHI - Mathur, Charu Arora; Ashtt, Rashmi (ShodhKosh: Journal of Visual and Performing Arts, 2026)
Urban green spaces (UGS) are widely acknowledged as critical infrastructures supporting public health, environmental sustainability, and social wellbeing. However, growing evidence suggests that their benefits are not equitably experienced across gender groups. This study examines gendered patterns of use across different hierarchies of urban green spaces in Delhi using systematic activity mapping. Empirical observations were conducted in four parks located in Rohini, North-West Delhi, representing regional, district, and neighborhood-level green spaces. Activities were recorded across weekdays and weekends during morning and evening periods and categorized into active and passive uses, disaggregated by gender. The findings reveal persistent gender disparities across all park hierarchies. Active recreational zones—including jogging tracks, open gyms, and sports courts—are consistently male-dominated irrespective of park scale. Female participation is concentrated in passive and social activities such as walking, seating, children’s play, and group interaction. Women’s presence increases during evenings and weekends, indicating that temporal accessibility, crowd density, and perceived safety strongly influence usage. Notably, neighborhood parks exhibit the highest degree of gender imbalance, highlighting everyday spatial exclusion rather than occasional access barriers. The study demonstrates that overall footfall is an inadequate indicator of inclusivity; instead, selective activity-based usage patterns provide a more accurate assessment of gender sensitivity. Based on empirical evidence, the paper proposes a gender-responsive planning framework emphasizing visibility, comfort-oriented infrastructure, mixed-use zoning, and temporal flexibility. The research contributes to urban planning discourse by offering data-driven insights to support equitable and inclusive design of urban green spaces in Delhi.